Intraoperative Fluoroscopic Imaging to Treat Cam Deformities: Correlation With 3-Dimensional Computed Tomography. (June 2014) - Ross, James R.; Bedi, Asheesh; Stone, Rebecca M.; Sibilsky Enselman, Elizabeth; Leunig, Michael; Kelly, Bryan T.; Larson, Christopher M.
Background: In the diagnosis and surgical treatment of cam-type femoroacetabular impingement (FAI), 3-dimensional (3D) imaging is the gold standard for detecting femoral head-neck junction malformations preoperatively. Intraoperative fluoroscopy is used by many surgeons to evaluate and verify adequate correction of the deformity. Purpose: (1) To compare radial reformatted computed tomography (CT) scans with 6 defined intraoperative fluoroscopic views before surgical correction to determine whether fluoroscopy could adequately depict cam deformity, and (2) to define the influence of femoral version on the clock-face location of the maximum cam deformity on these views. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: A consecutive series of 50 hips (48 patients) that underwent arthroscopic treatment for symptomatic FAI by a single surgeon were analyzed. Each patient underwent a CT scan and 6 consistent intraoperative fluoroscopy views: 3 views in hip extension and 3 views in hip flexion of 50°. The alpha angles of each of the fluoroscopic images were compared with the radial reformatted CT using a 3D software program. Femoral version was also defined on CT studies. Statistical analysis was performed using the Student t test, with P < .05 defined as significant. Results: Fifty-two percent of patients were male, average age 28 years (range, 15-56 years). The maximum mean alpha angle on fluoroscopy was 65° (range, 37°-93°) and was located on the anteroposterior (AP) 30° external rotation (ER) fluoroscopy view. In comparison, the mean CT-derived maximum alpha angle was 67° and was located at 1:15 ( P = .57). The mean clock-face positions of each of the fluoroscopy views (standardized to the right hip) were AP 30° internal rotation, 11:45; AP 0° (neutral) rotation, 12:30; AP 30° ER, 1:00; flexion/0° (neutral) rotation, 1:45; flexion/40° ER, 2:15; and flexion/60° ER, 2:45. Increased femoral anteversion (>20°) was associated with a significant change in the location of the maximum alpha angle (1:45 vs 1:15; P = .002). Conclusion: The described 6 fluoroscopic views are very helpful in localization and visualization of the typical cam deformity from 11:45 to 2:45 and can be used to reliably confirm a complete intraoperative resection of cam-type deformity in most patients. These views correlate with preoperative 3D imaging and may be of even greater importance in the absence of preoperative 3D imaging.